2018
DOI: 10.5539/ass.v14n10p1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Service Quality Dimensions on Students’ Satisfaction in University of Medical Sciences and Technology (UMST) Hostel Accommodation (Sudan)

Abstract: This paper aims to examine the effects of service quality dimensions on students’ satisfaction in University of Medical Sciences and Technology (UMST) students’ hostel accommodation in Sudan. It is based on an empirical study conducted at one of the Sudanese Private University. A quantitative method was employed. Out of 367, there were 200 questionnaires were returned represented 55% of the study response rate. SPSS version 22 and AMOS version 21.0 were used in the analysis the collected da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Other studies in other developing countries have shown that many factors determine the rental value and choice of accommodation among the students in tertiary institutions. For instance, Omar and Arbab (2018) considered the effects of the perceived mediating value on the relationship between the service quality dimensions and students' satisfaction in the University of Medical Sciences and Technology's Hostel Accommodation, Sudan, and revealed that there was a significant positive influence of perceived value on student's satisfaction of hostel accommodation in Sudan's tertiary institutions. Nimako and Bondinuba (2013) examined the student accommodation quality (SAQ) in College of Technology Education, Kumasi (COLTEK) and Kumasi Polytechnic (K-Poly) in Ghana, and noted that there was an unfavourable rating of the bathroom, security, toilet, access to transport, entertainment, kitchen and hostel fee based on the consideration of SAQ.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in other developing countries have shown that many factors determine the rental value and choice of accommodation among the students in tertiary institutions. For instance, Omar and Arbab (2018) considered the effects of the perceived mediating value on the relationship between the service quality dimensions and students' satisfaction in the University of Medical Sciences and Technology's Hostel Accommodation, Sudan, and revealed that there was a significant positive influence of perceived value on student's satisfaction of hostel accommodation in Sudan's tertiary institutions. Nimako and Bondinuba (2013) examined the student accommodation quality (SAQ) in College of Technology Education, Kumasi (COLTEK) and Kumasi Polytechnic (K-Poly) in Ghana, and noted that there was an unfavourable rating of the bathroom, security, toilet, access to transport, entertainment, kitchen and hostel fee based on the consideration of SAQ.…”
Section: Introductionmentioning
confidence: 99%